Biomechanical Comparison of Four Methods of Fixation of a Polymeric Cranial Cruciate Ligament in the Canine Femur and Tibia - Barnhart, Matthew D.; Bufkin, Brian W.; Litsky, Alan S. (Veterinary and Comparative Orthopaedics and Traumatology, 2019)
Objective The aim of this study was to compare the biomechanical properties of four different methods of artificial cranial cruciate ligament fixation in canine cadaveric tibias and femurs.Methods Femurs and tibias from skeletally mature large breed canine cadavers were assigned into four fixation groups: group 1, 4.5-mm interference screw (IS); group 2, 4.5-mm IS and 4.0-mm screw and spiked washer (SW); group 3, 5.0-mm IS; group 4, 5.0-mm IS + SW.Results The mean ultimate load was significantly greater for femur fixations than for tibias, when a SW was added, and for 5.0-mm IS compared with 4.5-mm sizes. There was also a significant interaction between SW and IS size. A SW significantly increased stiffness, a 5.0-mm IS in femurs provided more stiffness than 4.5-mm IS and was greater than 5.0-mm IS in tibias. In tibias, a 4.5-mm IS was stiffer than a 5.0-mm IS and a 4.5 IS + SW had greater stiffness than a 5.0-mm IS + SW. Groups 1 to 3 and tibias in group 4 failed by artificial ligament pullout. Nine femurs in group 4 failed by fracture, 5 by artificial ligament pullout, and 1 by artificial ligament tearing.Clinical Significance A 5.0-mm IS + SW provided superior artificial ligament fixation strength in femurs and tibias compared with a 4.5-mm IS without SW. Overall, artificial ligament fixation with 5.0-mm IS in femurs had the mechanical characteristics that most closely matched those reported in normal canine cranial cruciate ligaments.
Keywords: biomechanics; cruciate ligament repair techniques; ligaments; canine; interference screw